Treatment Patterns and Survival Outcomes of Prostate Cancer in Bangladeshi Patients - Arafat, Mohammad Ali; Bhuiyan, Mohammed Nazrul Islam; Akhtaruzzaman, Muhammed; Rana, Masud; Mahmud, Ashik; Ahmed, Adnan; Khan, Sozib (Community Based Medical Journal, 2025)
Prostate cancer is a growing health burden among Bangladeshi men, yet there is limited research on treatment patterns and survival outcomes in this population. Understanding the clinical management and prognostic factors is crucial for improving patient care. This study aimed to analyze the treatment modalities and survival outcomes of patients with prostate cancer. This purposive cross-sectional study was conducted from January 2022 to December 2024, including 86 histopathologically confirmed prostate cancer patients at the Bangladesh Medical College, Dhaka, Bangladesh. Data on demographics, clinical staging, treatment modalities (surgery, radiotherapy, hormone therapy, chemotherapy), and survival were collected from hospital records and patient interviews. Statistical analysis was performed using SPSS version 23.0, with Cox regression to identify prognostic factors. This study analyzed 86 prostate cancer patients (mean age 68.4 years), with 65.1% presenting at advanced stages (III-IV). Most (72.1%) received androgen deprivation therapy, while only 7.0% underwent radical prostatectomy. Median survival was 34.5 months, significantly shorter for Stage IV (22.5 months). Advanced stage (HR=3.12), high PSA (HR=2.10), and treatment delays >6 months (HR=2.34) independently predicted mortality. Prostate cancer in Bangladesh is predominantly diagnosed at advanced stages, leading to poor survival outcomes. Early detection, timely treatment, and improved access to multidisciplinary care are urgently needed to enhance prognosis and reduce mortality among Bangladeshi patients. CBMJ 2025 July: vol. 14 no. 02 P:115-120